2013
DOI: 10.3109/09638288.2013.797512
|View full text |Cite
|
Sign up to set email alerts
|

Expanded and revised gross motor function classification system: study for Chinese school children with cerebral palsy

Abstract: The Chinese version of the GMFCS-ER is a valid measure of functional ability in school children with CP and reliable enough for use by Chinese healthcare providers and parents. Effects of environmental and personal factors should be considered when practicing GMFCS-ER assessment. Implications for Rehabilitation Cerebral palsy. Research about GMFCS-ER is needed to promote a more extensive use of GMFCS-ER in China for school children with CP. The Chinese version of the GMFCS-ER is a valid measure of functional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…When the reliability of the Thai family report of the GMFCS was tested in communities, we found high overall interrater reliability (ICC 0.90, 95% CI 0.88-0.92) between special-education teachers and caregivers in children with CP aged 2 to 12 years. 14 The response rate in our study was 68% (25/37), which is an acceptable rate of participation, and 97% of responders used the Thai GMFCS-FR correctly, indicating that the Thai GMFCS-FR can be simply and conveniently used in the community. The current study initially reported reliability between special-education teachers and caregivers, while previous studies investigated the reliabilities of the GMFCS-FR between health professionals and families.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…When the reliability of the Thai family report of the GMFCS was tested in communities, we found high overall interrater reliability (ICC 0.90, 95% CI 0.88-0.92) between special-education teachers and caregivers in children with CP aged 2 to 12 years. 14 The response rate in our study was 68% (25/37), which is an acceptable rate of participation, and 97% of responders used the Thai GMFCS-FR correctly, indicating that the Thai GMFCS-FR can be simply and conveniently used in the community. The current study initially reported reliability between special-education teachers and caregivers, while previous studies investigated the reliabilities of the GMFCS-FR between health professionals and families.…”
Section: Discussionmentioning
confidence: 51%
“…Excellent reliabilities of the GMFCS-E&R and an overall ICC ranging between 0.84 and 0.92 were found in this prior study. 14 The response rate in our study was 68% (25/37), which is an acceptable rate of participation, and 97% of responders used the Thai GMFCS-FR correctly, indicating that the Thai GMFCS-FR can be simply and conveniently used in the community. The GMFCS-FR is definitely a useful tool for both caregivers and teachers to communicate effectively and plan an optimal goal and assistance for young children with CP.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…The scale comprises five dimensions divided by 88 items, with a total score of 264(16). This tool has been validated in the Chinese population(17,18). (II) GMFCS: the GMFCS is a five-level classification system, with level I indicating the best voluntary movement and level V representing the worst voluntary movement(19,20).…”
mentioning
confidence: 99%